Ninth Five Year Plan 1997-2002 and Annual Plan-1997-98 Draft Proposals Volume II Part - XI - General Services Government of Meghalaya - Planning Commission (Planning Commission, 1997)
The original outlay fixed for the Eighth Plan (1992-97) was Rs.250-00 lakhs. the outlay based on the Annual plan allocation during the five years of the plan is Rs.448.OO lakhs and if this is converted to 1991-92 prices, the outlay based on the Annual plan allocations will be Rs.357.00 lakhs. The main developmental activities are (I) Construction of multi-storied building at Shillong and Residential quarters al Government branch Press. Tura (ii) Purchase of machineries and equipments for Government Presses and State Assembly Press.
Government of Meghalaya, Planning Department